Generation and characterization of CD19-iCre mice as a tool for efficient and specific conditional gene targeting in B cells - Tomoharu Yasuda (Nature Portfolio, 2021)
Abstract The Cre/loxP system is a powerful tool for generating conditional gene knockout (KO) mice and elucidate gene function in vivo. CD19-Cre and Mb1-iCre transgenic mice are commonly used for generating B cell-specific KO mice and investigate the development, as well as the physiological and pathophysiological roles of B cells. However, the CD19-Cre line low efficiency and the Mb1-iCre line occasional ectopic recombination represent challenges for their use. Thus, we developed a CD19-codon-improved Cre (CD19-iCre) knock-in mouse with the T2A-iCre sequence inserted into the Cd19 locus, just before the stop codon. The CD19-iCre mice were compared with existing models, crossed with the Rosa26-EYFP reporter mice, and their recombination activity in B cells carrying different Cre alleles was assessed. CD19-iCre mice showed more effective Cre recombination in the early B cell developmental stages compared with the CD19-Cre mice. The efficiencies of the CD19-iCre and Mb1-iCre lines were similar; however, the B lineage-specific recombination was more stringent in the CD19-iCre line. Furthermore, the utility value of the CD19-iCre model was superior than that of the CD19-Cre mice regarding deletion efficiency in IL10-floxed mice. Thus, the CD19-iCre line is a valuable tool for highly efficient gene targeting specific to the B cell compartment.